Hubungan Kepemilikan SIM C dengan Kejadian Kecelakaan Lalu Lintas pada pelajar SMA di Wonokromo Kota Surabaya - Dwi Ratnasari; Lucia Yovita Hendrati (Universitas Airlangga, 2023)
Background: The increase in the number of motorized vehicles causes high number of traffic accidents in Indonesia. East java has a very high number of road accidents. This is become a concern for the government of the Republic of Indonesia. Surabaya become city with the highest accident rate. Objectives: The purpose of this research is the author wants to analyze the correlation between riding license (SIM C) ownership with the incidence of motorbike traffic accidents in high school students in Wonokromo Sub-district Surabaya. Methods: This study was an observational study that examines variables at a certain point in time so that a cross sectional study design was used in this research. The number of students who became respondents in this research were 114 students who were drawn from the population using a two-stage random sampling method. Chi-square was used to researching the correlation between two variables which are driving license ownership and the incidence of traffic accident Results: The result in that analysis showed that p=0,022 and RR=2,245, which means there was a relationship between those two variables. Conclusions: Riders are encouraged to ride their motorbike after having riding license (SIM C), because having a riding license is the parameter of a person having competence in riding both in theory and practice.